Characteristics of pediatric adverse drug reaction reports in the Japanese Adverse Drug Event Report Database - Aoi Noda; Takamasa Sakai; Taku Obara; Makoto Miyazaki; Masami Tsuchiya; Gen Oyanagi; Yuriko Murai; Nariyasu Mano (BMC, 2020)
Abstract Background There are no reports on investigations of the characteristics of adverse drug reaction (ADR) reports for pediatric patients in the Japanese Adverse Drug Event Report database (JADER) and the utility of database for drug safety surveillance in these patients. Method We aimed to evaluate ADR reports for pediatric patients in the JADER. We used spontaneous ADR reports included in the JADER since April 1, 2004, to December 31, 2017, which was downloaded in April 2018. In a total of 504,407 ADR reports, the number of spontaneous reports was 386,400 (76.6%), in which 37,534 (7.4%) were unknown age reports. After extraction of 27,800 ADR reports for children aged < 10 and 10-19 years, we excepted for ADR reports associated with a vaccine (n = 6355) and no-suspected drug reports (n = 86). A total of 21,359 (4.2%) reports were finally included in this analysis. Results More than half of the ADR reports were for children aged < 10 years. Approximately 30% of ADR reports had multiple suspected drugs, which did not differ by age. The percentages of fatal outcomes of ADRs among patients aged < 10 and 10-19 years were 4.7 and 3.9%, respectively. The most frequently reported drug, reaction, and drug-reaction pair were oseltamivir, abnormal behavior, and oseltamivir and abnormal behavior, respectively. Conclusion We clarified the characteristics of ADR reports for Japanese children by using the JADER. ADR report databases, especially those for pediatric patients, are valuable pharmacovigilance tools in Japan and other countries. Therefore, a proper understanding of the characteristics of the ADR reports in the JADER is important. Additionally, potential signals for ADRs in pediatric patients should be monitored continuously and carefully.